PERBEDAAN PRODUKSI ASI SEBELUM DAN SESUDAH PIJAT OKSITOSIN DAN PERAWATAN PAYUDARA PADA IBU NIFAS DI RSUD dr. R. GOETENG TARUNADIBRATA PURBALINGGA - Prasanti Adriani (Viva Medika, 2017)
The achievement of exclusive breastfeeding in Indonesia have not reached the expected number that is equal to 80%. According to a report in 2012 IDHS achievement of exclusive breastfeeding was 42%. Meanwhile, according to a report from the Provincial Health Office in 2013, coverage breastfeeding 0-6 months is only 54.3%. Dr. R. Goeteng Tarunadibrata Purbalingga a C class hospitals have inpatient and outpatient sufficient to Purbalingga regency. Medical personnel are competent and dedicated in health care as well as Mother Hood Safe program implemented in dr. R. Goeteng Tarunadibrata postpartum mothers should assist in increasing the production of milk to support exclusive breastfeeding programs that are beneficial to the baby. It can also support the raise coverage-exclusive breastfeeding from 46.1% to 80% as targeted work program Purbalingga Health Department. The purpose of this study was to analyze differences in milk production before and after the massage and treatment of breast oxytocin on postpartum mother in dr. R. Goeteng Tarunadibrata Purbalingga. The benefits of this research is to help postpartum mothers in increasing milk production so as to give exclusive breastfeeding for the baby. Target outcomes in this study are published in the national journal ISSN air, contribute to the development of knowledge about the increased production of milk in puerperal women, and enrichment of teaching materials on the subjects of midwifery care for women. Design of this research is quantitative descriptive approach one group pretest-posttest design. The sample in this study 30 for women. The results of the study milk production difference before and after the massage and treatment of breast oxytocin on postpartum mother in dr. R. Goeteng Tarunadibrata Purbalingga that there is a relationship between oxytocin and treatment of breast massage to breast milk in milk production in the postpartum mother postpartum room Bogenvile dr. R. Goeteng Tarunadibrata Purbalingga 2016 Ï-value is 0.004 <Î± (0.05). Keywords: milk production, oxytocin massage, breast care